The role of governance and infrastructure in moderating the effect of resource rents on economic growth - Simplice Asongu; Samba Diop; Ekene Emeka; Amarachi O. Ogbonna (African Governance and Development Institute (AGDI), 2024)
This study investigates how governance and infrastructure moderate the effect of natural resource rents on economic growth using a sample of 110 countries, including 47 African countries from 2000 to 2018. The empirical evidence is based on Panel Smooth Transition Regressions(PSTR). The following findings are established. First, the nexus between economic growth and natural resources is not linear and the underlying non-linearity is contingent on existing infrastructural and governance levels. Second, evidence of a "natural resource curse" is apparent in countries with extremely low levels of governance and infrastructural development. Third, the favorable effect of natural resources on economic growth requires a governance threshold of -1.210 and an infrastructure threshold of 2.583, indicating that countries with governance and infrastructure levels higher than these values tend to benefit much more from the wealth of natural resources. With high levels of the transition variables (governance and infrastructure), the established thresholds are low and situated between the 5 thand the 10th percentiles. Countries identified below the established thresholds are mainly from Africa. Policy implications are discussed with specific emphasis on African countries.
Keywords: H10; Q20; Q30; O11; O55; 330; Natural Resources; Economic Growth; Governance; Infrastructure; Threshold; Panel Smooth Transition Regressions; Generalised Method of Moments; Panel